2018
DOI: 10.3390/molecules23051212
|View full text |Cite
|
Sign up to set email alerts
|

Novel Imidazole Aldoximes with Broad-Spectrum Antimicrobial Potency against Multidrug Resistant Gram-Negative Bacteria

Abstract: In the search for a new class of potential antimicrobial agents, five novel N-substituted imidazole 2-aldoximes and their six quaternary salts were evaluated. The antimicrobial activity was assessed against a panel of representative Gram-positive and Gram-negative bacteria, including multidrug resistant bacteria. All compounds demonstrated potent in vitro activity against the tested microorganisms, with MIC values ranging from 6.25 to 50.0 μg/mL. Among the tested compounds, two quaternary compounds (N-but-3-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…[18] For instance, Kalhor et al reported a convenient method for the synthesis of imidazole derivatives by involving benzil, aldehyde, and ammonium acetate promoted by Fe 3 O 4 -loaded sulfonated zeolite. [19] Moreover, several catalytic techniques such as the use of InCl 3 .3H 2 O, [20] nanocrystalline-sulphated zirconia, [21] DABCO (1,4-diazabicyclo[2.2.2]octane), [22] nano-TiCl 4 . SiO 2 , [23] nano-SnCl 4 .SiO 2 , [24] HClO 4 -SiO 2, [25] PEG-400, [26] SiO 2 -Pr-SO 3 H, [27] and Ce(SO 4 ) 2 .4H 2 O [28] have been devised for the efficient synthesis of these moieties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] For instance, Kalhor et al reported a convenient method for the synthesis of imidazole derivatives by involving benzil, aldehyde, and ammonium acetate promoted by Fe 3 O 4 -loaded sulfonated zeolite. [19] Moreover, several catalytic techniques such as the use of InCl 3 .3H 2 O, [20] nanocrystalline-sulphated zirconia, [21] DABCO (1,4-diazabicyclo[2.2.2]octane), [22] nano-TiCl 4 . SiO 2 , [23] nano-SnCl 4 .SiO 2 , [24] HClO 4 -SiO 2, [25] PEG-400, [26] SiO 2 -Pr-SO 3 H, [27] and Ce(SO 4 ) 2 .4H 2 O [28] have been devised for the efficient synthesis of these moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Their several synthetic analogues possess numerous biological properties, i.e. , anti‐inflamatory, antimicrobial, anticancer, antitubercular, anti‐dengue, anti‐analgesic, anthelmintic, antimycotic, antitumor, and antibacterial activities . Also, the imidazole nucleus has displayed a noteworthy role in some advanced areas of technology such as biological imaging, glucagon receptors, fluorescence labelling agents, modulators of p ‐glycoprotein (P‐gp)‐mediated multidrug resistance (MDR), and chromophores for nonlinear optic systems (NLOS)…”
Section: Introductionmentioning
confidence: 99%
“…It is found that pyrazole and imidazole have the wide spectrum of antimicrobial evaluation owing to because the existence of nitrogen atom in fivemembered rings which acts by inhibiting cell wall synthesis or DNA (Deoxyribose nucleic acid) damage [59][60][61] . The antimicrobial activity of these heterocyclics attracted various scientists to attach pyrazole and imidazole rings with the indole nucleus to prevent the problem of microbial resistance.…”
Section: Evaluation Of Indole Compoundsmentioning
confidence: 99%
“…Preliminary antimicrobial screening of the water extract and extracts obtained with different organic solvents was performed using the disc diffusion assay according to CLSI procedure as previously described [21]. Briefly, 100 µl of suspension containing 10 6 colony-forming units (cfu/ml) of bacterial cells was spread on a Mueller Hinton agar (Becton Dickinson, Sparks, MD, USA).…”
Section: Growth Inhibition By Disc Diffusion Assaymentioning
confidence: 99%